Developing Urdu Stories to Address Articulation Errors in Children - Nasir, Faiza; Iftikhar, Nayab; Jabeen, Zahra (UMT Education Review, 2025)
The recent study centered on the development and standardization of Urdu stories as an intervention tool to address articulation errors. A mixed method design was employed, consisting of two phases. Phase I utilized qualitative methods, focused on story development and content validation, while Phase II used quantitative method and involved standardization and data analysis. Stories were developed by compiling age appropriate vocabulary from PTB (Punjab Textbook Board) books for the targeted sounds /g/, /k/, /chh/, /kh/ and /ph/ at initial, middle and final position of the word in Urdu language. Additionally, pictures of the stories were developed. For content validation, even speech and language pathologists and three Urdu language experts were consulted. The feedback obtained from these experts was then integrated into the stories and pictures to finalize them. Content validity was assessed through I-CVI, with scores ranging from 0.8 to 1, indicating high level of agreement among experts. In the second phase the finalized stories were applied on the sample of 200 typically developing Urdu speaking children within the age range of 3 to 7 years. Sample was selected through purposive sampling. The Cronbach’s alpha value ranging from 0.93-0.98>0.78 indicated high internal consistency. The mean score of Item’s difficulty lie within the range of 3.00 to 5.00. Results revealed that the developed stories were reliable and age appropriate and can be used as an intervention tool to address articulation errors in Urdu-speaking children.